An online story of electronics 1 (ELE232) utilizing MOOC / Norizan Ahmed ...[et al.] - Ahmed, Norizan; Che Kar, Siti Aishah; Wan Chek, Wan Ahmad Kusairi; Shafie, Rosmawati; Mahzan, Najwa Nasuha (Universiti Teknologi MARA Cawangan Kelantan, 2018)
An online platform for Electronics 1 (ELE232) course in UiTM Terengganu which contains fundamental knowledge of circuit theory is proposed. This platform is to introduce an online learning approach, to develop online assessments and to improve student’s skills plus their comprehensive ability onto topics related; a) theoretically; semiconductor material, b) practically; diode applications (i.e: calculation), and c) both theoretically and practically; BJTs and FETs.These are the main objectives in applying Massive Open Online Courses (MOOC) into the learning course. With android and IOS system, MOOC’s technology helps teachers and learners in being responsive anytime and anywhere by sharing lessons’ videos, perform circuit activities and more along with some cool awesome features. The interactive and intriguing materials integrated in MOOC for ELE232 resulting in better understanding of the principle of electronics among students.